Associations Between 20-Year Lipid Variability Throughout Young Adulthood and Midlife Cognitive Function and Brain Integrity. Issue 1 (11th April 2021) - Zeki Al Hazzouri, Adina; Caunca, Michelle R; Jawadekar, Neal; Grasset, Leslie; Elfassy, Tali; Odden, Michelle C; Wu, Chenkai; Elbejjani, Martine; Launer, Lenore; Yaffe, Kristine
Abstract: Background: Little is known about long-term lipid variability in young adulthood in relation to cognitive function and brain integrity in midlife. Method: We studied 3 328 adults from the Coronary Artery Risk Development in Young Adults. We defined low- and high-density lipoprotein (LDL and HDL) variability as the intraindividual standard deviation of lipid measurements over 20 years of young adulthood (1985–2005). Cognitive tests were administered in 2010. Brain scans were performed in 2010 on 714 participants. To facilitate comparison, cognitive tests and brain metrics were z -scored. Results: Mean age at baseline was 25.4 years. Higher 20-year LDL variability was associated with worse verbal memory in midlife (β = −0.25, 95% CI: −0.42, −0.08), adjusted for important covariates. Higher 20-year HDL variability was associated with worse processing speed in midlife (β = −0.80, 95% CI: −1.18, −0.41) and brain integrity, for example, smaller total brain volume (β = −0.58, 95% CI: −0.82, −0.34) and worse total brain fractional anisotropy (β = −1.13, 95% CI: −1.87, −0.39). Conclusions: Higher long-term lipid variability in adulthood was associated with worse cognition and brain integrity in midlife, in a relatively young cohort.